1993
DOI: 10.1093/eurheartj/14.10.1349
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of  -adrenergic receptors on mononuclear leukocytes induced by dobutamine treatment in patients with congestive heart failure

Abstract: (+/-)-Dobutamine is a positive inotropic drug usually used to improve ventricular function in patients with congestive heart failure (CHF). However, it has been found that haemodynamic responses to dobutamine become blunted during continuous treatment. In this study we determined the time-dependent changes of beta-adrenergic receptors in CHF patients treated with dobutamine. Seven CHF patients received a continuous intravenous infusion of dobutamine (5 micrograms.kg-1 x min-1) for 96 h. Blood samples were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…In line with the present findings, a 24 h levosimendan infusion has previously been shown to maintain the haemodynamic effects at a similar level at 24 and 48 h,10 with the effects lasting for about 7 days 14. The haemodynamic effects of dobutamine may diminish owing to tachyphylaxis,15,16 but in the present study this was not seen, and cardiac index and PCWP were at similar levels at 24 and 48 h in the dobutamine group.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the present findings, a 24 h levosimendan infusion has previously been shown to maintain the haemodynamic effects at a similar level at 24 and 48 h,10 with the effects lasting for about 7 days 14. The haemodynamic effects of dobutamine may diminish owing to tachyphylaxis,15,16 but in the present study this was not seen, and cardiac index and PCWP were at similar levels at 24 and 48 h in the dobutamine group.…”
Section: Discussionsupporting
confidence: 89%
“…However, a notable exception to the correlation between agonist strength and rate of down-regulation is evidenced by the data from dobutamine treatments that show a slightly greater rate of down-regulation of ␤-ARs than the coupling efficiency would predict. Consistent with our results, dobutamine has been shown to be a potent down-regulator of ␤-ARs in leukocytes when administered for treatment of congestive heart failure (Teng et al, 1993). Furthermore, Blevins et al (2000) have shown that dobutamine displays unusual properties with regard to a quantitative analysis of GTP shifts relative to the other agonists.…”
Section: Agonistsupporting
confidence: 91%
“…Also, the down-regulation of beta-adrenergic receptors with prolonged dobutamine infusion [88] has clinical implications leading to development of tolerance [89]. Dobutamine is not hemodynamically as effective in patients receiving beta-blockers as those who are not.…”
Section: Dobutaminementioning
confidence: 99%